A review on indoor airborne transmission of COVID-19– modelling and mitigation approaches. (1st April 2023) - Rayegan, Saeed; Shu, Chang; Berquist, Justin; Jeon, Jisoo; Zhou, Liang (Grace); Wang, Liangzhu (Leon); Mbareche, Hamza; Tardif, Patrique; Ge, Hua
Abstract: In the past few years, significant efforts have been made to investigate the transmission of COVID-19. This paper provides a review of the COVID-19 airborne transmission modeling and mitigation strategies. The simulation models here are classified into airborne transmission infectious risk models and numerical approaches for spatiotemporal airborne transmissions. Mathematical descriptions and assumptions on which these models have been based are discussed. Input data used in previous simulation studies to assess the dispersion of COVID-19 are extracted and reported. Moreover, measurements performed to study the COVID-19 airborne transmission within indoor environments are introduced to support validations for anticipated future modeling studies. Transmission mitigation strategies recommended in recent studies have been classified to include modifying occupancy and ventilation operations, using filters and air purifiers, installing ultraviolet (UV) air disinfection systems, and personal protection compliance, such as wearing masks and social distancing. The application of mitigation strategies to various building types, such as educational, office, public, residential, and hospital, is reviewed. Recommendations for future works are also discussed based on the current apparent knowledge gaps covering both modeling and mitigation approaches. Our findings show that different transmission mitigation measures were recommended for various indoor environments; however, there is no conclusive work reporting their combined effects on the level of mitigation that may be achieved. Moreover, further studies should be conducted to understand better the balance between approaches to mitigating the viral transmissions in buildings and building energy consumption. Highlights: Comprehensive review on COVID-19 community and airborne transmission modeling. Reviewed applications of these approaches by building types and mitigation measures. Novelty explained by comparing to previous COVID-19 reviews. Limitations of existing modeling approaches were detailed and compared. Lack of study on combined mitigations and energy impacts during post-COVID-19 era.